Ticagrelor vs. clopidogrel for coronary microvascular dysfunction in patients with STEMI: a meta-analysis of randomized controlled trials - Li, Yike; Ye, Zixiang; Guo, Ziyu; Xie, Enmin; Wang, Min; Zhao, Xuecheng; Liu, Mei; Li, Peizhao; Yu, Changan; Gao, Yanxiang; Zheng, Jingang (Frontiers in Cardiovascular Medicine, 2023)
Purpose Approximately half of ST-segment elevation myocardial infarction (STEMI) patients who undergo revascularization present with coronary microvascular dysfunction. Dual antiplatelet therapy, consisting of aspirin and a P2Y12 inhibitor (e.g., clopidogrel or ticagrelor), is recommended to reduce rates of cardiovascular events after STEMI. The present study performed a pooled analysis of randomized controlled trials (RCTs) to compare effects of ticagrelor and clopidogrel on coronary microcirculation dysfunction in STEMI patients who underwent the primary percutaneous coronary intervention. Methods The PubMed, Embase, Cochrane Library, and Web of Science databases were searched for eligible RCTs up to September 2022, with no language restriction. Coronary microcirculation indicators included the corrected thrombolysis in myocardial infarction (TIMI) frame count (cTFC), myocardial blush grade (MBG), TIMI myocardial perfusion grade (TMPG), coronary flow reserve (CFR), and index of microcirculatory resistance (IMR). Results Seven RCTs that included a total of 957 patients (476 who were treated with ticagrelor and 481 who were treated with clopidogrel) were included. Compared with clopidogrel, ticagrelor better accelerated microcirculation blood flow [cTFC = −2.40, 95% confidence interval (CI): −3.38 to −1.41, p < 0.001] and improved myocardial perfusion [MBG = 3, odds ratio (OR) = 1.99, 95% CI: 1.35 to 2.93, p < 0.001; MBG ≥ 2, OR = 2.57, 95% CI: 1.61 to 4.12, p < 0.001]. Conclusions Ticagrelor has more benefits for coronary microcirculation than clopidogrel in STEMI patients who undergo the primary percutaneous coronary intervention. However, recommendations for which P2Y12 receptor inhibitor should be used in STEMI patients should be provided according to results of studies that investigate clinical outcomes.